West Bank and Gaza : Education Sector Analysis - Impressive Achievements Under Harsh Conditions and the Way Forward to Consolidate a Quality Education System - World Bank (Washington, DC, 2014)
The Palestinian Education System comprises a Mandatory Basic Cycle covering Grades 1 to 10, divided into the Preparation Stage (Grades 1 to 4) and the Empowerment Stage (Grades 5 to 10). Optional Secondary Education covers Grades 11 and 12, with the option of general secondary education, and a few vocational secondary schools. Post secondary education is offered in 11 universities, (10 private and one public), 11 technical colleges (4 government, 2 UNWRA, 4 public and 1 private) which offer mainly 4 year programs. In addition there are 19 community colleges (1 government, 9 public, 2 UNRWA, and 7 private) that offer mainly two-year diploma courses in technical and commercial specializations. The Ministry of Education and Higher Education (MOEHE) developed in 1999 a five-year Education Development Plan for the period 2000-2005. This was the first time after the establishment of the Palestinian Authority in 1994 that the MOEHE developed a National Plan with a unified vision for the Palestinian education system from pre-school to secondary education.